PENGARUH PUPUK ORGANIK PADAT DAN JENIS BAMBU TERHADAP PERTUMBUHAN BAMBU PETUNG (DEDROCALAMUS ASPER) DAN BAMBU HIAS (BAMBUSA BALCOOA) - Nanda, Rizki; Muslimin, Muslimin; Zulkaidhah, Zulkaidhah; Rahmawati, Rahmawati (Universitas Tadulako, 2021)
The use of fertilizers is needed to supply nutrients for plant growth. The use of organic fertilizers on bamboo plants is still rarely done. The purpose of this study was to determine the effect of the dose of solid organic fertilizer and the type of bamboo that gave the best effect and the interaction of the application of solid organic fertilizer and the type of bamboo produced by tissue culture. This research was conducted from July to September 2018, located at the Faculty of Forestry, Tadulako University. The research method used a completely randomized design (CRD) with a factorial pattern, namely the first type of bamboo, B1 petung bamboo and B2 ornamental bamboo. The second factor is solid organic fertilizer P0 = 0 g/clump P1 = 250 g/clump P2 = 500 g/clump P3 = 750 g/clump. With ten treatment combinations of tissue cultured types of bamboo and a dose of solid organic fertilizer. Each treatment was repeated three times to produce 30 experimental units. The results showed that the dose of solid organic fertilizer had a very significant effect on the increase in height and number of bamboo leaves. Furthermore, the treatment of bamboo species had a very significant effect on the growth of the number of leaves but not significantly on other parameters. Meanwhile, the interaction effect between bamboo species and the dose of solid organic fertilizer significantly affected the increase in clump height. The interaction treatment of ornamental bamboo (Bambusa balcooa) + solid organic fertilizer 1000 g/clump (B2P4) gave an average increase in clump height (4.81 cm) significantly different from petung bamboo + solid organic fertilizer 250 g/clump (B1P0), bamboo ornamental + solid organic fertilizer 0 g/clump (B2P0), ornamental bamboo + solid organic fertilizer 250 g/clump (B2P1), and ornamental bamboo + solid organic fertilizer 750 g/clump (B2P3).Keywords: Organic Fertilizer, Petung Bamboo, Ornamental Bamboo